sqrt(-2) = i sqrt(2)

sqrt(-36) = i sqrt(36) = 6i

You need to use brackets to make it clear exactly what you mean, but lets suppose these are a=[3+sqrt(5)]/2, and b=[3-sqrt(5)]/2Edit also can someone show me an example of writing a quadratic equation with these solutions?

3 + squareroot 5 / 2 , 3 - squareroot 5 / 2 . ?

then one such quadratic equation is:

(x-a)(x-b)=0

Now expanding the left hand side of this we have:

x^2 + (-a-b)x + ab = x^2 + (-6/2)x + (3^2+5)/4 = x^2 - 3x + 7,

so the quadratic simplifies to:

x^2 - 3x + 7=0

RonL